Dear god - Norhafsah Hamid (Iman Publication, 2020)
In Dear God (the sequel to Letters To God), author Norhafsah Hamid weaves a tender story of young love, second chances and a soul that is lost, seeking to find what has been missing in his heart all along. Jonah thought he had everything a guy could ever needed to sail through life. A family that is supportive, cool friends that made university life a breeze and looks that won him the affection of many girls. Except for one - Sarah. An encounter with Sarah made Jonah realise that there is more than the one revolving around him. Jonah decides to brave the path least taken in the search for the meaning of eternal contentment. He found himself connecting to the One that he has long forgotten since he was little. Is there still hope for him? 'Dear God, grant me strength., prayed Jonah silently.